OPTIMIZING THE ROLE OF PARENTS IN STRENGTHENING MORAL EDUCATION IN THE DIGITAL ERA (PIONIR: JURNAL PENDIDIKAN, 2025)
This research aims to analyze the role of parents in strengthening children's moral education in the digital era and identify the challenges faced in the process. The method used in this study is a descriptive qualitative approach through in-depth interviews and questionnaires to teachers and parents in the elementary school environment. The results of the study show that the role of parents is still not optimal in accompanying children, especially related to the use of digital technology which increasingly dominates children's daily lives. The three main problems found are the low digital literacy of parents, lack of communication and emotional involvement with children, and lack of supervision of digital content consumed by children. As a result, children experience a decline in moral values such as good manners, empathy, and self-control. This research emphasizes the importance of synergy between families, schools, and communities in creating a supportive environment.Keywords: Digital age, Moral education, The role of parents
Keywords: Digital age; Moral education; The role of parents.